Nursing students' perceptions of clinical relevance and engagement with bioscience education: A cross-sectional study of undergraduate and postgraduate nursing students. (April 2021) - Barton, Matthew J.; Bentley, Steven; Craft, Judy; Dupen, Oliver; Gordon, Christopher; Cayanan, Elizabeth A.; Kunst, Elicia; Connors, Amanda; Todorovic, Michael; Johnston, Amy NB.
Abstract: Background: Bioscience in nursing education covers a broad range of disciplinary areas (anatomy, physiology, pathophysiology and pharmacology) and underpins clinical assessment and critical thinking in nursing practice. This is imperative for patient safety and favourable patient outcomes. In nursing programs for registration, most bioscience content is taught during the early phases of the program and little incorporated into postgraduate nursing programs. Objectives: The aim of this study was to explore student's perceived relationship between clinical relevance and engagement (attention and time) with bioscience content, by surveying undergraduates and postgraduate nursing students. Design: This sequential mixed methods study included two phases. Methods: The first phase comprised of focus group interviews from one Australian University. Thematic analysis of these data, coupled with existing literature, informed the second study phase; a quantitative questionnaire. Participants: Focus group interviews included N = 30 students from one tertiary site; 10 from each year level. The questionnaire was administered to nursing students undertaking undergraduate nursing studies (1st, 2nd & 3rd years), and postgraduate nursing studies. Results: Nursing students (n = 406) across three Australian universities (four programmes) completed the questionnaire. The clinical relevance of bioscience was widely appreciated; 91.6% of undergraduate nursing students and 98.5% of postgraduate nursing students indicated that every nurse must have a good understanding of bioscience. However, there was an inverse relationship between engagement with bioscience and timing in the curriculum, as 50% of undergraduate nursing students indicated that bioscience content took up too much of their time, compared to only 20% of postgraduate nurses (odds ratio 0.27 [0.16–0.46], p < 0.001). Conclusion: Nursing students' perceptions of the clinical relevance of bioscience for their career strongly corresponds with their progression through their studies. Unfortunately, as students progress to the later years of their nursing education, their engagement with formal bioscience education decreases. This poses the question 'Are we delivering bioscience content to nursing students at the appropriate time?'